Peningkatan Kemampuan Siswa Kelas XI SMA Negeri 1 Toari dalam Menulis Naskah Drama Melalui Model Pembelajaran Discovery Learning - Sukma Sukma; Syarifuddin Tundreng; La Alu (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This research was motivated by students’ limited understanding of the intrinsic elements of drama, including theme, plot, character, setting, and moral value, as well as drama structure, namely prologue, dialogue, and epilogue. Students also experienced difficulty adapting short stories into drama scripts. This study aimed to describe the improvement of students’ ability to write drama scripts adapted from short stories through the discovery learning model. This research used Classroom Action Research based on the Kemmis and McTaggart model, conducted in three stages: pre-action, cycle I, and cycle II. The subjects were 21 students of class XI A at SMA Negeri 1 Toari. Data were collected through observation, drama script writing tests, and documentation. The results showed improvement in each cycle. In cycle I, the average score reached 70.48, classical completeness was 33.3%, and student activity was 52.91%. In cycle II, the average score increased to 80.43, classical completeness reached 80.95%, and student activity increased to 83.86%. The cumulative increase in the average score reached 39.51%. These findings prove that discovery learning effectively improves students’ ability to write drama scripts adapted from short stories.